4.Doprowadź do najprostrzej postaci:(^3=potęga)

b)2x(x^2-3x+7)+3(x^3-2x^2+4)=

d) -3(x^3+4x-2)+2x(x^2-3x)=
________________________________________

5.Doprowadź do najprostrzej postaci:

b) 1½(2a-3b-c)-2½(a-2b+c)

d)3(0,6a-1,1b+0,9c)-4(0,3a+1,2b-0,3c)
________________________________________

6.Doprowadź do najprostrzej postaci:

a)4(2½a- 1¼b)-3(2a-1½b)-2(-1¼ a- 1 3/4b)

b)2½(a-2b)-¼ (3a-5b)+ 1¼ (2a-3b)

c)0,4(3a+2b)-0,3(-6a+b)-0,7(2a-3B)

d)-1,3(-2a+3b)-2,1(a-2b)-0,5(5a-2b)

2

Odpowiedzi

  • mono
  • Początkujący
2009-12-03T16:32:43+01:00
4.B) 2x^3-6x^2+14x+3x^3-6x^2+12=6x^3-12x^2+14x+12
d)-3x^3-12x+6+2x^3-6x^2=-x^3-6x^2-12x+6

5.
b)2 1/2a-3 1/2b-1 1/2c- 2 1/2a+4 1/2b -2 1/2c=1 1/2b+1 1/2c
d)1,8a-3,3b+2,7c-1,2a-4,8b+1,2c=0,6a-8,1b+3,9c

6.
a)8 1/2a -4 1/4b-6a+3 1/2b-2 1/4a +2 3/4b=1/2a+2b
b)2 1/2a-4 1/2b-3 1/4a+5 1/4b+2 1/4a-3 1/4b=3/4a -3/2b
c)1,2a+0,8b+1,8a-0,3b-1,4a+2,1b=1,6a+2,6b
d)2,6a-3,9b-2,1a+4,2b-2,5a+b=-2a+0,3b

Najlepsza Odpowiedź!
2009-12-03T16:57:49+01:00
4.
b)2x(x^2-3x+7)+3(x^3-2x^2+4)=2x³-6x²+14x+3x³-6x²+12=5x³-12x²+14x+12

d) -3(x^3+4x-2)+2x(x^2-3x)=-3x³-12x+5+2x³-6x²=x³-12x+5-6x²

5.
b) 1½(2a-3b-c)-2½(a-2b+c)=3/2(2a-3b-c)-5/2(a-2b+c)=3a-9/2b-3/2c-5/2a+5b-5/2c=1/2a+1/2b-4c
d)3(0,6a-1,1b+0,9c)-4(0,3a+1,2b-0,3c)=1,8a-3,3b+2,7c-1,2a-4,8b+1,2c=0,6a-8,1b+3,9c

6
a)4(2½a- 1¼b)-3(2a-1½b)-2(-1¼ a- 1 3/4b)=10a-5b-6a+4,5b+2,5a+3,5b=6,5a+4b

b)2½(a-2b)-¼ (3a-5b)+ 1¼ (2a-3b)=5/2a-5b-3/4a+5/4b+10/4a-15/4b=17/4a+2 2/4b

c)0,4(3a+2b)-0,3(-6a+b)-0,7(2a-3B)=1,2a+0,8b+1,8a-0,3b-1,4a+2,1b=1,6a+2,6b

d)-1,3(-2a+3b)-2,1(a-2b)-0,5(5a-2b)=2,6a-3,9b-2,1a+4,2b-2,5a+1b=-2a+1,3b